Accuracy of pacing during breaststroke swimming using a novel pacing device, the Aquapacer™ - Thompson , K. G.; MacLaren, D. P. M.; Lees, A.; Atkinson, G. (Journal of Sports Sciences, 2002)
Generally, swimmers pace themselves using their own judgement and the poolside clock during swimming training, fittness testing protocols or scienti® c investigation. The Aquapacer is a new pacing device that can be used to pace the swimming speed or stroke rate of the swimmer. The aims of this study were to determine if breaststroke swimmers could pace accurately during submaximal swimming using a poolside clock (Study 1) and the Aquapacer (Study 2), at swimming speeds at, just above and just below maximal 200 m time-trial speeds (using the Aquapacer, Study 3) and under three diþ erent race pacing conditions (using the Aquapacer, Study 4). Between 8 and 15 male national or club standard 200 m breaststroke swimmers participated in each of the studies. The swimmers in Study 2, despite being less well trained than the swimmers in Study 1 and part of a more heterogeneous group in terms of swimming performance, repeatedly demonstrated less random error in pacing, suggesting that the Aquapacer may be preferable to the poolside clock when swimmers are being required to pace accurately. The AquapacerÔ also enabled swimmers to pace accurately at racespecific swimming speeds (until fatigue precluded them from holding pace) (Study 3), and through a change in pace at race-specific speeds (Study 4), which suggests that it may be of use in entraining racing strategies.